Correlations between Parity and Marriage Age with Incidence of Cervical Cancer at Gunung Jati Hospital, Cirebon, Indonesia - Oktaviani, Maya; Permata, Yukke Nilla; Sutrisno, Wildan Arismunandar (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Cervical cancer is one of the leading causes of death among women in Indonesia, and factors such as parity and age at marriage are believed to play a significant role in increasing the risk of developing this disease. Aims: Examine the relationship among parity and age at marriage with the incidence of cancer of cervix by describing the age distribution, parity, age at marriage, and histopathological features of cancer of cervix patients at Gunung Jati Hospital in Cirebon, Indonesia. Methods: This study utilized an analytical observational approach with a cross-sectional design. It analyzed secondary data, specifically the medical records of cancer of cervix patients at Gunung Jati Hospital in Cirebon from 2022 to 2023. A total of 47 patients were selected through total sampling. The Spearman correlation test was employed for statistical analysis to determine the correlation between the variables. Results: The majority of cervical cancer patients were multiparous (70.2%), had a marriage age of < 20 years, and exhibited histological findings of Squamous Cell Carcinoma Keratinizing (48.9%). No correlation was found among parity and the occurrence of cancer of cervix (p = 0.450; p > 0.05). However, a significant association was observed among age at marriage and cancer of the cervix occurrence (p = 0.010; p < 0.05). Conclusion: The results of the study are expected to provide insight into the importance of reproductive factors in the prevention of cervical cancer, as well as recommendations for more effective reproductive health policies. Received: 02 October 2024 | Reviewed: 15 October 2024 | Revised: 09 November 2024 | Accepted: 30 November 2024.